Bicentennial man - Columbus, Chris; Kazan, Nicholas (Touchstone Home Video Distributed by Buena Vista Home Entertainment ; distributed in the Philippines by Magnavision, 2000)
A comedy about an android "household appliance" robot who just wants to be a regular guy.